SISTEM INFORMASI GEOGRAFIS ( SIG) PEMETAAN TOKO BANGUNAN DI TEMBILAHAN BERBASIS WEB - Jepridin; Usman (Indragiri Islamic University, 2022)
Indragiri Hilir Regency has many locations of Building Shops scattered in several places in Indragiri Hilir Regency. However, not all of the people of Indragiri Hilir Regency know the locations of these Building Shops. Only a small number of people know the location of the building shop. Therefore, the researchers tried to build a Geographic Information System application for mapping the location of building shops in Indragiri Hilir Regency, with the intention that the people of Indragiri Hilir Regency would know information about the location and location of Building Shops scattered in the Indragiri Hilir Regency area. The purpose of the research is to present information about the object where the building shop is located in the Indragiri Hilir district and to design a web-based geographic information system application that can provide accurate data needed by parties who need information. This research method uses the Waterfall model. Waterfall development model is a systematic and sequential development model (sequential). In this study, researchers used pieces analysis to analyze several matters. The analysis and design phase is one of the tools to create a system. The goal is to minimize the weaknesses of the system that will be made. In the system design process, researchers use modeling with the UML (Unified Modeling Language) approach. A web shop mapping geographic information system has been built that makes it easy for users to obtain information about building shops in Tembilahan quickly, accurately, and can be accessed by anyone, anywhere, anytime, regardless of distance and time. The building shop in Tembilahan is web-based using the Google Maps API. For the database using XAMPP and compiling scripts/programming code using a text editor Visual Code Studio, Notepad++ and the programming language used is PHP and for CSS using Materialize.